2010
DOI: 10.1016/j.ygeno.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel stress-regulated microRNAs from Oryza sativa L.

Abstract: MicroRNAs (miRNAs) are a type of small non-coding RNA found in eukaryotes. They play a key role in gene expression by down-regulating gene expression and are involved in the environment stress response in plants. Although a large number of miRNAs have been identified from Arabidopsis, few studies have focused on Oryza sativa miRNAs, especially on stress-related miRNAs. Five cDNA libraries of small RNAs from rice seedlings treated with cold, dehydration, salinity, and abscisic acid (ABA), as well as wild-type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 44 publications
2
58
1
2
Order By: Relevance
“…[32,52] SGN-U236908 (TIR) was repressed in all three tomato genotypes. The degradation of TIR mRNAs may subsequently prevent depression of auxin-signalling pathway.…”
Section: ããmentioning
confidence: 97%
See 1 more Smart Citation
“…[32,52] SGN-U236908 (TIR) was repressed in all three tomato genotypes. The degradation of TIR mRNAs may subsequently prevent depression of auxin-signalling pathway.…”
Section: ããmentioning
confidence: 97%
“…Tang et al [31] found up-regulation of miR167 and role of trans-acting short-interfering RNAÀauxin response factor (tasiRNAÀARF) in regulating the auxin-signalling pathway and possibly in the developmental response to cold stress in wheat. In rice, Jian et al [32] found several cold-regulated miRNAs by direct cloning and sequencing. Zhang et al [33] identified 28 cold responsive miRNAs in Brachypodium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been documented that several miRNAs are associated with nutrient homeostasis under phosphate or sulfate depletion conditions (Jones- Fujii et al, 2005;Aung et al, 2006;Bari et al, 2006;Hsieh et al, 2009;Lundmark et al, 2010;Nilsson et al, 2010). Although most of these observations were made in Arabidopsis, a few studies also reported stress-related miRNAs in rice (Oryza sativa; Bari et al, 2006;Zhao et al, 2007Zhao et al, , 2009aSanan-Mishra et al, 2009;Jian et al, 2010;Li et al, 2011). However, genome-wide analysis of rice small RNA data has not been successful for the identification of new abiotic stress-regulated miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Although miRNAs are initially discovered using genetic screening technology (Lee et al, 1993;Wightman et al, 1993), this method is limited as it is expensive, time consuming and dominated by chance (Zhang et al, 2006b). Direct cloning of miRNAs, followed by construction and sequencing of a small RNA library, has been successfully employed to identify miRNAs in plants (Feng et al, 2009;Jian et al, 2010;Sunkar et al, 2005;Yao et al, 2007). However, only abundant miRNA genes can be easily detected by cloning or Northern blot.…”
Section: Introductionmentioning
confidence: 99%